Modelling and PID controller design for a quadrotor unmanned air vehicle - Salih, A.L.; Moghavvemi, M.; Mohamed, H.A.F.; Gaeid, K.S. (2010)
this paper presents the modelling of a four rotor vertical take-off and landing (VTOL) unmanned air vehicle known as the quadrotor aircraft. The paper presents a new model design method for the flight control of an autonomous quad rotor .The paper describes the controller architecture for the quadrotor as well. The dynamic model of the quad-rotor, which is an under actuated aircraft with fixed four pitch angle rotors, will be described. The Modeling of a quadrotor vehicle is not an easy task because of its complex structure. The aim is to develop a model of the vehicle as realistic as possible. The model is used to design a stable and accurate controller. This paper explains the developments of a PID (proportional-integral-derivative) control method to obtain stability in flying the Quad-rotor flying object. The model has four input forces which are basically the thrust provided by each propeller connected to each rotor with fixed angle. Forward (backward) motion is maintained by increasing (decreasing) speed of front (rear) rotor speed while decreasing (increasing) rear (front) rotor speed simultaneously which means changing the pitch angle. Left and right motion is accomplished by changing roll angle by the same way. The front and rear motors rotate counter-clockwise while other motors rotate clockwise so that the yaw command is derived by increasing (decreasing) counter-clockwise motors speed while decreasing (increasing) clockwise motor speeds.